2022
DOI: 10.1021/acs.jchemed.1c01145
|View full text |Cite
|
Sign up to set email alerts
|

Development and Evaluation of a Survey to Measure Student Engagement at the Activity Level in General Chemistry

Abstract: Student engagement is an important consideration when incorporating active learning activities into a classroom. To facilitate the large-scale assessment of students' engagement in activities, a survey measure must first be developed and evaluated. Therefore, the goal of this study was to create a self-report measure of student engagement for use with active learning activities in general chemistry classes. The Activity Engagement Survey (AcES) was modified from an existing survey of engagement of middle and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 35 publications
3
33
0
Order By: Relevance
“…One of the major findings of this study was the conflation in how students perceive behavioral and cognitive engagement. This finding, combined with support from our quantitative study, 29 implies that these two dimensions of engagement cannot be measured and evaluated separately. Therefore, it is suggested that future studies combine these dimensions when seeking to evaluate students' engagement in learning activities.…”
Section: Implications For Researchsupporting
confidence: 51%
See 1 more Smart Citation
“…One of the major findings of this study was the conflation in how students perceive behavioral and cognitive engagement. This finding, combined with support from our quantitative study, 29 implies that these two dimensions of engagement cannot be measured and evaluated separately. Therefore, it is suggested that future studies combine these dimensions when seeking to evaluate students' engagement in learning activities.…”
Section: Implications For Researchsupporting
confidence: 51%
“…Additionally, a recent quantitative study by Naibert and Barbera in higher-education, which assessed student engagement in active learning activities of general chemistry students, found further evidence for combining behavioral and cognitive engagement into a combined behavioral/cognitive dimension. 29 The results of our qualitative and quantitative studies provide support for students' perceiving a large overlap between behavioral and cognitive engagement when asked specifically to think about the specific activities. Therefore, it may be that students conflate the two dimensions when the focus is on engagement in a specific activity instead of the class as a whole.…”
Section: Social Engagementmentioning
confidence: 52%
“…Engagement was assessed using the BC-E and BC-E-S versions of the Activity Engagement Survey (AcES). 14 The BC-E AcES measure includes 15 items related to students overall engagement, with 10 of those items also related to behavioral/cognitive engagement (e.g., I stayed focused during today's activity) and 5 items related to emotional engagement (e.g., I looked forward to today's activity). The BC-E-S AcES includes 19 items related to students' overall engagement: the same 15 items from the BC-E AcES, as well as 4 items also related to social engagement (e.g., I built on other students' ideas during today's activity).…”
Section: Survey Itemsmentioning
confidence: 99%
“…Evidence in support of internal structure validity provides confidence that the items relate to the construct as expected. 23,24 The BC-E and BC-E-S AcES bifactor models relate each item to an overall engagement factor, as well as to the relevant behavioral/cognitive, emotional, or social engagement factor (see Naibert and Barbera 14 ). In a previous related study, 14 evidence of internal structure validity was found for the data collected in the remote environment (2020−2021 academic year) (n = 1248) using the BC-E AcES bifactor model with a negative method factor.…”
Section: Internal Structure Validitymentioning
confidence: 99%
See 1 more Smart Citation